THE USE OF CHEMICAL ADDITIVES FOR FISHERIES PRODUCT PRESERVATION - Mr Syamdidi (Research and Development Center for Marine and Fisheries Product Processing and Biotechnol, 2012)
Preservation is a common practice in processed food products including fisheries product.The purpose of preservation in food is not only maintain the quality of food but also to prolong theshelf life of food itself. Preservatives can be divided into two groups i.e. natural and chemicalpreservatives. The chemical preservatives potentially used in fishery industry are nitrite, sulfurdioxide, benzoic acid and, sorbic acid. These preservatives have their own characteristics oninhibition of microorganisms. Food characteristic such as pH, and aw are the key factors on theactivity of antimicrobial agent.